RD50-MPW3: a fully monolithic digital CMOS sensor for future tracking detectors. (28th February 2023) - Sieberer, P.; Zhang, C.; Bergauer, T.; Casanova, R.; Irmler, C.; Karim, N.; Mazorra de Cos, J.; Pilsl, B.; Vilella, E.; ,
Abstract: The CERN-RD50 CMOS working group develops the RD50-MPW series of monolithic high-voltage CMOS pixel sensors for potential use in future high luminosity experiments such as the HL-LHC and FCC-hh. In this contribution, the design of the latest prototype in this series, RD50-MPW3, is presented. An overview of its pixel matrix and digital readout periphery is given, with discussion of the new structures implemented in the chip and the problems they aim to solve. The main analogue and digital features of the sensor are already tested and initial laboratory characterisation of the chip is presented.